(untitled) (Stamford Journal of Pharmaceutical Sciences, 2012)
The present study aimed to provide information about the common cancer types and respective predisposing risk factors among the Bangladeshi cancer patients from different cancer hospitals located in Dhaka city. A survey is conducted to establish a relationship between common cancer types and predisposing risk factors. A nationwide representative sample of 610 Bangladeshi cancer patients were asked about their medical history, life-style, eating habit and genetic risk factors in relation to cancer prevention, as a part of omnibus survey. Interviews were conducted with 610 subjects (339 men and 271 women). Among the male, the leading cancers were lung (76 patients), followed by mouth and oropharynx (66 patients), stomach (41 patients) etc. Among the female, breast cancer (64 patients) ranked the topmost position, followed by cervix (48 patients), ovary (37 patients), mouth and oropharynx (34 patients). Among 11 risk factors among men candidates, the attributable fraction of cancer causing by tobacco smoking was considered highest (68.14%), followed by betel leaf (67.55%). For most risk factors, attributable fraction responses were higher in women than in men. 14 risk factors among women cancer patients, the attributable fraction of cancer causing by viral and bacterial diseases (39.10%) was highest, followed by obesity (37.10%) and then chronic disease (37.03%) excluding food habit. Our results suggest that awareness of the attributable fraction of cancer causes in the Bangladeshi cancer patient tends to be dominated by tobacco smoking, food habit, cancer causing infection, men and women hygiene, and reproductive history among females rather than genetic factors. DOI: http://dx.doi.org/10.3329/sjps.v4i2.10439 S. J. Pharm. Sci. 4(2) 2011: 35-41